Analisis Faktor-Faktor Penyebab Kredit Macet Oleh Nasabah Sektor Usaha Agribisnis (Studi Kasus Pada BPR Aceh Besar) - Kurnia Maiza Satria; Suyanti Kasimin; Teuku Makmur (Jurnal Ilmiah Mahasiswa Pertanian, 2016)
The purpose of this study to determine the characteristics of their loan borrowers Aceh Besar in the sector of agribusiness that has bad credit and to determine the factors that cause the bad loans by businesses agribusiness BPR Aceh Besar. The location of this research is in the rural banks (BPR) in Aceh Besar Jln. Banda Aceh Medan KM. 9 NO.5 Lambaro District Ingin Jaya, Aceh Besar district. The object of this research is great Aceh BPR customers who experienced a delay in the repayment of credit, especially in the agri-business customers in this study the effect of non-payment of loan repayments due to several factors including: the age of the borrower, business experience, number of dependents, level of education and business turnover. Results showed characteristics of respondents who experienced bad credit in Aceh Besar BPR average age was 37 years, with a junior high education level graduates, have experience in trading business an average of 12 years and the number of dependents who owned as many as 2 people. Main types of work vegetables and grocery merchants. When viewed from the start of this business is that most of 2009 with the number of 4 and a maximum of 2004 as many as one person. While the results of the analysis showed that age, and level of education has a negative correlation to the occurrence of bad loans, while the level of business experience, business turnover of dependents and have a positive relationship to the causes of bad loans by the merchant in the agribusiness sector. Keywords: Bad Debt, Customer, Agribusiness Sector